MANAJEMEN PEMBELAJARAN PENDIDIKAN ANAK USIA DINI DI TK RUTOSORO KECAMATAN GOLEWA KABUPATEN NGADA FLORES NUSA TENGGARA TIMUR - Efrida Ita (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2018)
This study aims to describe the learning management of early childhood education in Rutosoro kindergarten, namely 1) planning of learning, 2) implementation of learning, 3) assessment of learning. This study was qualitative study. This study was done in Rutosoro kindergarten. The study design was educational ethnography. The subjects of this study were the headmaster, teachers and students of Rutosoro kindergarten. The methods of data collection in this study were interview, observation and documentation. The data analysis in this study using the analysis of interactive model developed by Miles and Huberman namely data collection, data reduction, data display and conclusion. The result of study shows that 1) the planning of learning is made in the form of syllabus, the semester planning, weekly activities planning, daily activities planning. In making the learning planning the kindergarten teachers need to consider the level of children development, the children development aspects, the children’s needs, the children’s interest, and the children’s characteristics, 2) the implementation of learning in Rutosoro kindergarten begins with the welcoming of the children by the teachers, introduction (moving together, praying, presenting, questioning on themes and subthemes), core activities, eating and resting, closing. Implementation of learning using the methods adapted to the theme with the principle of playing while learning, and 3) the assessment of learning is done every time since the children come to the school till the children go back to home through the assignment, conversation, observation, performance, work, and portofolio.